Analysis of Morphological Development Due to the Industrial Development in Majalaya District, Bandung Regency - Hana Sugiastu Firdaus; Arwan Putra Wijaya; Nadhea Ramadhani (Journal of Applied Geospatial Information, 2022)
Majalaya District is one of the areas close to the Upper Citarum River. Agricultural land in some areas in the district is converted for industrial development. This causes a decrease in the quantity and quality of agricultural land. The existence of land conversion can affect morphological changes. The study aims to determine the pattern of land use changes and determine the morphology of regional development in 2014 and 2021 in Majalaya District, Bandung Regency. The spatial analysis method is done by on-screen digitization, descriptive analysis and figure ground analysis. The results of this study are the pattern of land use changes using figure ground method and descriptive analysis of the morphology in Majalaya District between 2014 and 2021. Based on the results of figure ground analysis calculation on the solid classification of industrial class in 2014 it was 182,310 Ha (25%), while in 2021 it was 258,905 Ha (27.19%). Morphological analysis of the district is based on the pattern of building plots, road network patterns and building systems from 2014 to 2021. The analysis results show the district morphology of octopus/star shaped cities and unpatterned cities. This form is influenced by the development of industrial buildings in Majalaya District which causes the morphology of the area also to change. Keywords: Figure Ground, Industry, Land Use Change, Majalaya District, Morphology